2022
DOI: 10.1242/dmm.049544
|View full text |Cite
|
Sign up to set email alerts
|

Snrpb is required in murine neural crest cells for proper splicing and craniofacial morphogenesis

Abstract: Heterozygous mutations in SNRPB, an essential core component of the five small ribonucleoprotein particles of the spliceosome, are responsible for Cerebrocostomandibular Syndrome (CCMS). We show that Snrpb heterozygous embryos arrest shortly after implantation. Additionally, heterozygous deletion of Snrpb in the developing brain and neural crest cells models craniofacial malformations found in CCMS, and results in death shortly after birth. RNAseq analysis of mutant heads prior to morphological defects reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…In light of the effect of SNRPB on ER export, we hypothesized that loss of SNRPB might cause defects in trafficking of type-I collagen. We therefore performed immunofluorescence staining in neural crest tissue from wild type mice and Snrpb neural crest specific heterozygous ( Snrpb ncc+/- ), which we described recently(Alam et al , 2022). In the tissue of wild type mice, collagen-I was distributed mostly extracellularly and to some extent intracellularly (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In light of the effect of SNRPB on ER export, we hypothesized that loss of SNRPB might cause defects in trafficking of type-I collagen. We therefore performed immunofluorescence staining in neural crest tissue from wild type mice and Snrpb neural crest specific heterozygous ( Snrpb ncc+/- ), which we described recently(Alam et al , 2022). In the tissue of wild type mice, collagen-I was distributed mostly extracellularly and to some extent intracellularly (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that embryos with heterozygous loss of function mutation in Snrpb arrested at embryonic day (E) 8.5 (Alam et al ., 2022), indicating an early requirement for this gene during gastrulation. We also showed bone deformities in the craniofacial region of neural-crest cell Snrpb mutants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… ABSTRACT First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Sabrina Alam is first author on ‘ Snrpb is required in murine neural crest cells for proper splicing of genes essential for craniofacial morphogenesis ’, published in DMM. Sabrina is a PhD student in the lab of Dr Loydie A. Jerome-Majewska at McGill University, Montreal, Canada, investigating the role of splicing in the complexity of craniofacial development.…”
mentioning
confidence: 99%